Spin control : the White House Office of Communications and the management of presidential news - Maltese, John Anthony (UNC Press law publications., 1994)
Spin Control, originally published in 1992, chronicles the development of the powerful White House Office of Communications and its pivotal role in molding our perception of the modern presidency. In this new edition, John Maltese brings his analysis up to date with a chapter detailing the media techniques of the Bush administration, the 1992 presidential campaign (including the use of talk shows like 'Larry King Live'), and the early Clinton administration.